GENETIC ANALYSIS AND MOLECULAR INTERACTION OF UGPase IN SOME TUBER PLANTS RELATED TO GLUCOMANNAN PRODUCTION - Ulum, Badiul; Arumingtyas, Estri Laras; Kurniawan, Nia (Biotropika: Journal of Tropical Biology, 2013)
UGPase is an enzyme that affect the conformation of polysaccharide with Î² 1-4 bond. There are some differences interaction of UGPase enzyme with UDP-Glucose substrate in some tuber plants. So, the aim of this research are to observe the interaction of UGPase and UDP-G in some tuber plants and to observe the relationship among tuber plant based on UGPase sequence. Result of molecular docking shows the catalytic domain interaction of UGPase and UDP-G in substrate binding loop, lower energy free obtain from A. konjac is -5.06 kcal/mol, following by I. batatas and S. tuberosum is -4,60 dan -3,73 kcal/mol respectively. Interaction was stabilize by some interaction type, there are electrostatic and hydrogen in A. konjac and I. batatas, and hydrophobic in S. tuberosum. Sequence alignment of UGPase shows I. batatas and S. tuberosum relatively close than to A. konjac. Â  Key words: interaction, UDP-Glucose, UGPase